Vault run speeds - Sands, W. A. (Technique, 2000)
In order to study the maximum vault run speeds of top American female gymnasts, run-ups were recorded during the 1999 John Hancock U.S. Gymnastics Championships in Sacramento, Calif. Because of the constraints of a live event, spectators, television, and so forth, radar was chosen to study the vault run-ups during training and warm ups using a radar gun (Radar Sales, Inc.). The radar gun was capable of recording the movement of an object in 0.1 mile per hour (0.045 m/s) increments with a sampling rate 20 Hz (20 samples/s). The radar gun allowed data collection to occur while standing at the start of the vault run way and recording vault run-up speeds without interacting with the gymnast. Because the training and warm ups of the gymnasts were not under my control, I could not dictate the number of trials nor the type of vault performed by the gymnasts, although each was recorded. Multiple trials of the same vault were then averaged. Because of the nature of the competition rules, two different vaults were required for each athlete. The present analysis indicates that maximum vault run speed is not significantly related to score. However, this conclusion should not be generalized to all vaulting performances. The small population used for this analysis consisted of only Junior gymnasts at the 1999 John Hancock U.S. Gymnastics Championships-surely a very select and relatively homogeneous group. If a similar analysis was performed using these elite athletes and perhaps a number of Junior Olympic athletes, the resulting analysis would probably show a higher relationship between speed and score as younger, smaller, and slower athletes would likely score lower than their Junior Elite counterparts.